Integrating epigenomics into pharmacogenomic studies - Wei Zhang; R Stephanie Huang; M Eileen Dolan (Dove Medical Press, 2008)
Wei Zhang, R Stephanie Huang, M Eileen DolanSection of Hematology/Oncology, Department of Medicine, The University of Chicago, Chicago, IL 60637, USAAbstract: The goal of personalized medicine is to recommend drug treatment based on an individual’s genetic makeup. Pharmacogenomic studies utilize two main approaches: candidate gene and whole-genome. Both approaches analyze genetic variants such as single nucleotide polymorphisms (SNPs) to identify associations with drug response. In addition to DNA sequence variations, nongenetic but heritable epigenetic systems have also been implicated in regulating gene expression that could influence drug response. The International HapMap Project lymphoblastoid cell lines (LCLs) have been used to study genetic determinants responsible for expression variation and drug response. Recent studies have demonstrated that common genetic variants, including both SNPs and copy number variants (CNVs) account for a substantial fraction of natural variation in gene expression. Given the critical role played by DNA methylationin gene regulation and the fact that DNA methylation is currently the most studied epigenetic system, we suggest that profiling the variation in DNA methylation in the HapMap samples will provide new insights into the regulation of gene expression as well as the mechanisms of individual drug response at a new level of complexity. Epigenomics will substantially add to our knowledge of how genetics explains gene expression and pharmacogenomics.Keywords: epigenetics, DNA methylation, gene expression, pharmacogenomics, HapMap, drug response